PENGARUH TINGKAT PENDIDIKAN, TENAGA KERJA, PENDAPATAN ASLI DAERAH (PAD) DAN DANA ZAKAT TERHADAP PERTUMBUHAN EKONOMI DI EKS-KARESIDENAN SURAKARTA TAHUN 2016-2021 - Fikri, Wahyu Najib; Adhana, Ilham Fajar (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This study aims to determine the effect of the education level of local original income (PAD) workers and zakat funds on economic growth in the former Surakarta residency 2016-2021. This type of research is a quantitative method with an associative analysis approach. The population used in this study is data from the Central Statistics Agency (BPS) and the National Zakat Agency (BAZNAS) which contain the required variable data. The sampling technique uses saturated sampling technique, meaning that all populations are sampled. Data were obtained from secondary data obtained from the website of the Central Statistics Agency (BPS) to obtain data on education and workforce levels. Data analysis technique was performed using multiple linear regression. The results of the study show that (1) the level of education has a significant positive effect on economic growth. (2) Labor has a significant positive influence on economic growth. (3) Regional Original Income has a significant positive influence on economic growth. (4) Zakat has a significant positive effect on economic growth. Keywords: Education Level, Workforce, Regional Own Revenue, Zakat Funds, Economic Growth.